Evaluación del grado de microfiltración coronal de tres materiales de obturación provisional (cavit, iónomero de vidrio y óxido de zinc y eugenol) usados en cavidades con acceso endodóntico de dientes extraídos, estudio in vitro. Periodo marzo-julio 2016. - Ludeña Camacho, Ana María (2016)
The role of the temporary filling materials in endodontic is two folded; first of all it prevents the entry of saliva with microorganisms within the root canals, avoiding infection or reinfection of the same; second of all it prevents medicine to be placed within the pulp chamber and root canals escaping into the oral cavity, preserving the effectiveness of the medicine/ drug, this is why the seal ability of materials is temporary filling therefore is paramount and decisive in the success or failure of the endodontic treatment. The objective of this study is to determine the degree of microfiltration of temporary cavity cements, glass ionomer, zinc oxide and eugenol. Sixty healthy teeth were used, they were divided into three groups of 20 teeth for each of the respective groups respectively sealed with cavit, glass ionomer cement and zinc oxide and eugenol; to be placed in the incubator at 37◦C of temperature for 5 days; after that, they were immersed in blue methylene for 7 days, then they were cut longitudinally and evaluated in each degree of microfiltration using a rating scale of 0 to 3. The results showed that the glass ionomer, zinc oxide and eugenol are temporary restoration materials which are presented in a greater degree of microfiltration. Key Words: Temporary filling materials, marginal microfiltration.